The prevalence of rheumatic disease in a rural Coloured population in Namaqualand - Meyers, Orlando Llewellyn (Division of Rheumatology, 2017)
No epidemiological field studies of the rheumatic diseases have been undertaken in the Coloured population of South Africa. As a group they are genetically heterogenous and in comparative medicine they have tended to occupy an intermediate position between Black and White South Africans. A study of the nature and extent of rheumatic disease in this population group can make an important contribution. (i) The Coloured population is both simple, unsophisticated and rural, and on the other hand unquestionably urbanised. In this sense they provide a unique opportunity to study the prevalence of rheumatoid arthritis under rural and urban conditions. Such a study if it supports the rural/ urban differences which have been shown for Black South Africans will help to focus attention on the urban environment in the pathogenesis of rheumatoid arthritis. The same may be true of other rheumatic diseases such as systemic lupus erythematosus. On the other hand, data which is similar to that of other studies also has importance in reinforcing accepted ideas, and furthermore such a study affords an opportunity to test criteria of disease in different circumstances. This helps to define problems and ultimately aids in the refining of criteria. (ii) The planning of strategies for health services cannot hope to become adequate neither can the effectiveness of such health strategies be measured if the prevalence of an important group of diseases is not known. (iii) The teaching of under and postgraduates must also be influenced by the research conducted by a medical school, and in this way the provision and the planning of health services are aided. This study in a rural Coloured population forms the first of a series of studies in rural/urban living Coloured people. The rural study used as its universe the population of Rietpoort in Namaqualand, where 80 % of the adult population was seen.